Proactive early threat detection and securing SQL database with IBM QRadar and IBM Spectrum Copy data management, using IBM FlashSystem safeguarded copy - Sapkar, Tejas; Shingornikar, Shashank (IBM Blueprint, 2022)
This IBM® blueprint publication focuses on early threat detection within a database environment by using IBM QRadar®. It also highlights how to proactively start a cyber resilience workflow in response to a cyberattack or potential malicious user actions. The workflow that is presented here uses IBM Spectrum® Copy Data Management as orchestration software to start IBM FlashSystem® Safeguarded Copy functions. The Safeguarded Copy creates an immutable copy of the data in an air-gapped form on the same IBM FlashSystem for isolation and eventual quick recovery. This document describes how to enable and forward SQL database user activities to IBM QRadar. This document also describes how to create various rules to determine a threat, and configure and start a suitable response to the detected threat in IBM QRadar. Finally, this document outlines the steps that are involved to create a Scheduled Job by using IBM Spectrum® Copy Data Management with various actions.